Accuracy improvement of surface measurement through phase correction in spectrally resolved interferometer. (June 2023) - Zhang, Mengsi; Wang, Zhiyuan; Luo, Songjie; Ji, XuanXuan; Chen, Ziyang; Pu, Jixiong
Highlights: An algorithm is proposed to improve the surface profilemeasurement accuracy in spectral interferometer. Simulation is carried out to prove this algorithmhas the 96% possibility to correct the error in slope of the linear fitted phase and the 4% possibility to bring the additional minor errorunder the influence of three kinds of additive noise. For the measurement of a reflecting mirror, the maximum variation of the surface and the repeatability are optimized to 10 nm and 2.2 nm from 30 nm and 4.9 nm, respectively. For the measurement of a smooth profile with a step shape of nearly 3 μm height, the algorithm provides a surface variation less than 10 nm and minimum step height repeatability of 1.3 nm. Abstract: The spectrally resolved interferometer (SRI) is used to measure the surface profile by the linear fitting line of its phase distribution of spectral interference signal. However, the noise existed in the phase cannot be ignored if the nano-scale measurement accuracy is required. In this paper, a novel algorithm is proposed to improve the measurement accuracy by using the constant term oflinear fitting line of phase distribution in wavenumber domain. The simulations indicate that the algorithm achieves the similar measurement accuracy under the influence of three kinds of noise. Even though the proposed algorithm has the possibility of 4% to bring the additional minor error, it provides a better performance on measurement of entire surface in different SNRs compared with the other two common algorithms. In experiments, the variations of surface less than 10 nm and 30 nm and the repeatability of 2.2 nm and 4.9 nm are obtained in the measurements of a protected aluminium mirror with and without proposed algorithm. A smooth profile with a step shape of nearly 3 μm height is tested, where the maximum repeatability of step height and maximum magnitude of variations of the surfaces reaches to 3.8 nm and 10 nm from the 15.3 nm and 30 nm by using this algorithm. Both the simulations and experimental results demonstrate that the proposed algorithm is feasible for high-precision measurement.